Outcome of tap block in the cesarean section on postoperative pain (Texas Journal of Medical Science, 2022)
This paper focuses on the Outcome of tap block in the cesarean section on postoperative pain where 100 patients from different hospitals in Iraq were included and distributed into two groups, 50 patients, which included pregnant women who underwent tap block, 50 control groups, which included pregnant women who underwent other types of anaesthesia for caesarean section. In this study, the ages of the patients ranged from 28 to 43 years, and preliminary information was collected regarding age, weight, comorbidities, and the amount of morphine. In this study, pregnant women who underwent a caesarean section between August 2020 to October 2021 were included, and the data were analysed statistically by using IBM soft SPSS program and Microsoft Excel 2016 the results which found in this study were the incidence of pain in the immediate postoperative period was for 25 patients in the control group (95% CI: 90.9 - 94.2) and ten patients in the tap block group. The average reported pain intensity score was 4.5±0.2, and the pain intensity score was 4.5±0.2. The weakest is 0.5 ± 0.12. As for complications after caesarean section, the frequency of complications was found in the control group more than in the tap block patients' group, with a statistical significance found.